1999
DOI: 10.1099/00221287-145-10-2939
|View full text |Cite
|
Sign up to set email alerts
|

Two fatty acid Δ9-desaturase genes, ole1 and ole2, from Mortierella alpina complement the yeast ole1 mutation

Abstract: cerevisiae. This indicated that the M. alpina ∆9-desaturase had a substrate preference for stearic acid (18 :0) rather than palmitic acid (16 :0). Genomic clone ∆9-2 (ole2) also encoded a protein of 445 aa which had 86 % identity to the ∆9-1 and LM9 proteins and whose ORF also complemented the yeast ole1 mutation. The transcript from this gene could only be detected in one of the six M. alpina strains tested, suggesting that its expression may be strainspecific or induced under certain physiological conditions. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 33 publications
0
30
0
Order By: Relevance
“…S. cerevisiae strain L8e1 (MATa elo3∆ ::kanMX4 ole1∆ ::LEU2 leu2-3 leu2-112 ura3-52 his4) was constructed from L8-14C by PCR-mediated kanMX4 gene deletion of ELO3 as described below. M. alpina and S. cerevisiae strains were cultured as described previously (Wongwathanarat et al, 1999). M. alpina growth medium S2lowN was a modified version of S2GYE (MacKenzie et al, 2000) containing 0n01 % (w\v) yeast extract (Oxoid) and 0n01 % (w\v) NH % SO % .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…S. cerevisiae strain L8e1 (MATa elo3∆ ::kanMX4 ole1∆ ::LEU2 leu2-3 leu2-112 ura3-52 his4) was constructed from L8-14C by PCR-mediated kanMX4 gene deletion of ELO3 as described below. M. alpina and S. cerevisiae strains were cultured as described previously (Wongwathanarat et al, 1999). M. alpina growth medium S2lowN was a modified version of S2GYE (MacKenzie et al, 2000) containing 0n01 % (w\v) yeast extract (Oxoid) and 0n01 % (w\v) NH % SO % .…”
Section: Methodsmentioning
confidence: 99%
“…M. alpina growth medium S2lowN was a modified version of S2GYE (MacKenzie et al, 2000) containing 0n01 % (w\v) yeast extract (Oxoid) and 0n01 % (w\v) NH % SO % . In yeast feeding experiments, unsaturated fatty acids were added at a final concentration of 0n5 mM to medium containing 1 % (w\v) tergitol NP-40 (Sigma) (Wongwathanarat et al, 1999), whereas saturated fatty acids were first dissolved in 90 % (v\v) ethanol at a concentration of 1 mM and added to medium lacking tergitol to give a final concentration of 0n04 mM. In the latter, control cultures were supplemented with 3n6% (v\v) ethanol.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The enzyme was probably the most important for maintenance of proper membrane fluidity of living organismsm during the evolution. Wongwathanarat (1999) reported that the yeast Δ9-desaturase activity, compared with other fatty acid desaturases, was mostly involved to changing the membranes fluidity during temperature shift. Hsieh and Kou (2005) support this hypothesis with experiment with two fishes Ctenopharyngodon idella and Chanos chanos.…”
Section: δ9-desaturasementioning
confidence: 99%